Logical Relations Used in Anak Boru Saninain Simalungun Wedding Ceremony - Purba, Nurhasanah (International Journal of Culture and Art Studies, 2020)
The aims of this study is to find out the types of logical relations and the use of logical relations Anak Boru Sanina (ABS) in Simalungun wedding ceremony. This study was conducted by applying descriptive qualitative method. The source of data was taken from the utterances of Anak Boru Sanina (ABS) in Simalungun wedding ceremony. The result of this research was types of logical relations can be found in Anak Boru Sanina (ABS) are paratactic enhancement (34.78 %), hypotactic enhancement (30.43%), paratactic extension (14.49 %), paratactic elaboration (11.59%), hypotactic elaboration (4.34 %), hypotactic extension (2.89 %), and paratactic locution (1.44 %). Only seven of ten types of logical relations found in Anak Boru Sanina (ABS) utterances meanwhile three types that are missing are hypotactic locution, paratactic idea and hypotactic idea, because these types concern the relation between a mental or verbal clause and the content which its quotes or reported.